Географиялық билим бериўде жойбарлаў (проект) технологияларын қолланыў - Абдираманов, Ж.Б; Беласарова, Ш.М (SCIENCE and SOCIETY, 2023)
The article reveals the importance of technology training, that is, based on project technology in the de- velopment of knowledge, skills and creative thinking of secondary school students when teaching geography.
Keywords: project; innovative methods; pedagogical technologies; creative thinking; pedagogical cooperation; training cases; openning a dialogue